KECEMASAN BERG DALAM NOVEL DER VORLESER KARYA BERNHARD SCHLINK - LAILIA, MUFTADIATUL (UNIVERSITAS NEGERI SURABAYA, 2016)
This research is telling about Berg who was had anxiety that change Berg’s behaviuor. This research describe about anxiety type and effect of anxiety which Berg’s had in Der Vorleser’s novel by Bernhard Schlink. This research using the theory psychoanalysis of Sigmund Freud. According to Freud anxiety is the situation it is not fun is characterized by the physical symptoms that warned someone there will be a danger that threaten. Anxienty Freud divided into three parts that anxiety realistic, anxiety neurotic and anxiety moral. Anxiety realistic is anxiety will danger in the real world. Anxiety neuritik comes from within the individual between the impulse id (sexual impulse and aggressive impluse) that can not accepted  by ego and super ego. Moral anxiety is fear the sound of the heart of yourself. The fear of this appear when doing something that is not in accordance with the norms moral. The moral anxienty is the result of the conflict between id and super ego. The method used in this research is the descriptive qualitative which describes result of data analysis in the form of the words, phrase and a sentences that shows the anxienty Berg’s derived form Der Vorleser’s novel. The results of the research that shows Berg who was had  three types of anxienty is anxiety realistic, neurotic and moral. The anxienty this causes that change Berg’s behavior. At the beginning of the story, Berg is a young man who is introvert and difficult to socialize with his environment. When together with Hanna, Berg had anxiety. The anxiety happened continuously when Hanna left Berg. Berg had more anxiety because he remembered his moment with Hanna. After experiencing several anxieties, change Berg’s behaviuor. The change Berg’s behaviuor is confident, more mature and  trautor. Keywords: Anxiety, psychoanalysis, behavioral changes.